1997
DOI: 10.1007/bf02042723
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in the utilization of public mental health services in Washington State

Abstract: This study analyzed racial differences in the use of public outpatient mental health services in four regions of Washington State. Patients in this study were enrolled in the state's mental health management information system, which contains detailed information about patient characteristics and service utilization. There were distinct racial differences with respect to baseline characteristics, and even after adjusting for these characteristics and region of the state as well, racial differences in the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…The literature points towards specific barriers endemic to individuals residing in low-income urban areas, such as high treatment costs, lack of insurance, limited time and competing priorities, loss of pay from missing work, inconvenient or inaccessible clinic locations, limited clinic hours, transportation problems, and child care difficulties (Armstrong, Ishiki, Heiman, Mundt & Womack, 1984; Maynard, Ehreth, Cox., Peterson & McGann, 1997). For those caregivers with significant economic difficulties, seeking treatment may be seen as an additional financial burden (Hall, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The literature points towards specific barriers endemic to individuals residing in low-income urban areas, such as high treatment costs, lack of insurance, limited time and competing priorities, loss of pay from missing work, inconvenient or inaccessible clinic locations, limited clinic hours, transportation problems, and child care difficulties (Armstrong, Ishiki, Heiman, Mundt & Womack, 1984; Maynard, Ehreth, Cox., Peterson & McGann, 1997). For those caregivers with significant economic difficulties, seeking treatment may be seen as an additional financial burden (Hall, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic and qualitative studies (Armstrong et al 1984;Maynard et al 1997) have identified a number of practical barriers to service use by populations living on low incomes: cost; not being insured; limited time and competing priorities; loss of pay from missing work; inconvenient or inaccessible clinic locations; limited clinic hours; transportation problems; and child care difficulties. Psychological barriers to care may include the stigma of depression (Corrigan et al 2000), previous negative treatment experiences on the part of the woman with depression or members of her family and social network (McKay and Bannon 2004), and the burden of depression itself.…”
Section: Adding a Pre-treatment Engagement Session To Brief Iptmentioning
confidence: 99%
“…Potential patient barriers include: 1) practical barriers (e.g.,economic problems; lack of medical insurance, transportation, or childcare; competing priorities and limited time; inaccessible clinic locations); 20,21,22 2) cultural barriers (e.g.,clinician insensitivity to cultural values, preferred ways of coping, and beliefs about depression); 15,23,24 and 3) psychological barriers (e.g.,previous negative experiences with service use; 25 stigma of depression 26 ). Another barrier appears to be an avoidant or fearful attachment style, often resulting from exposure to childhood or domestic trauma 27,28 and characterized by strong self-reliance and/or distrust of others, potentially making it difficult to engagement in treatment.…”
Section: Introductionmentioning
confidence: 99%